Validation of the Portable Next-Generation VECTRA H2 3D Imaging System for Periocular Anthropometry - Fan, Wanlin; Guo, Yongwei; Hou, Xiaoyi; Liu, Jinhua; Li, Senmao; Ju, Sitong; Matos, Philomena Alice Wawer; Simon, Michael; Rokohl, Alexander C.; Heindl, Ludwig M. (Frontiers in Medicine, 2022)
Purpose: Portable three-dimensional imaging systems are becoming increasingly common for facial measurement analysis. However, the reliability of portable devices may be affected by the necessity to take three pictures at three time points. The purpose of this study was to evaluate the effectiveness of portable devices for assessing the periocular region. Methods: In 60 Caucasian volunteers (120 eyes), four facial scans (twice for each instrument) using the portable VECTRA H2 and static VECTRA M3 devices were performed; patients’ heads were kept straight, looking ahead, with a neutral facial expression. One assessor set 52 periocular landmarks in the periocular area of each image and subsequently assessed intra- and inter-device reliability by comparing two within-device measurements and one between-device measurement, respectively. Results: The mean absolute difference (MAD) (0.13 and 0.12 units), relative error of measurement (REM) (0.61% and 0.68%), technical error of measurement (TEM)(1.02 and 0.80 units), relative TEM (rTEM) (5.51% and 4.43%), and intraclass correlation coefficient (ICC) (0.89, 0.89) showed good intra-device reliability for M3 and H2; MAD (0.63, 0.62 units), REM (2.83%, 2.69%), TEM (1.31, 1.10 units), rTEM (7.62%, 5.57%) and ICC (0.79, 0.83) indicated that inter-device reliability deteriorated compared to intra-device reliability and that the inter-device reliability of the first scan (moderate) was lower than that of the average of the two scans (good). Conclusions: The portable VECTRA H2 device proved reliable in assessing most periocular linear distances, curve distances, and angles; some improvement in inter-device reliability can be achieved by using the average of two scans.